'Whole body' CT scanning following blunt multitrauma: a Delphi study. (26th December 2010) - Hunt, Paul
Abstract : Background: The 2007 NCEPOD report recommends the routine use of 'top-to-toe' scanning in the adult trauma patient if no immediate indication for intervention exists. No specific guidelines currently exist for the use of 'Whole Body' CT (WBCT) scanning following blunt multi-trauma. Current clinical practice relies on trauma team leader decision-making although a number of UK institutions have presented WBCT protocols and supporting data. However, there is a paucity of evidence with which to inform best clinical practice. Objective: The aim of this study was to explore the main issues regarding WBCT for blunt multi-trauma as the first stage of a wider research programme aiming to develop a WBCT protocol and recommendations for best clinical practice. A Delphi study was conducted in order to establish national and multidisciplinary consensus on a series of relevant statements which could be used to produce both clinical practice and organisational recommendations, and to highlight areas where further research was required. Methods: Invitations and follow-up questionnaires were sent to a representative sample of consultants working in the fields of Emergency Medicine, trauma surgery, anaesthesia, critical care and radiology from across the UK. A total of 160 statements were generated from the responses to these questionnaires, which contributors were then able to comment on and modify during two subsequent rounds before a list of final 'consensus' statements were agreed. Results: 18/18 of correspondents who replied to the initial invitation completed all three rounds of the study. The results demonstrated considerable agreement on the need for a formal WBCT protocol, evidence-based clinical indicators and an effective clinical governance structure. We present a full description of the consensus statements, initial recommendations and an original WBCT protocol. We believe this is the first systematic attempt to define and identify areas of best clinical practice regarding WBCT for blunt multi-trauma.